EDUKASI ENTREPRENEURIAL MARKETING BAGI KOPERASI PASCA PPKM COVID-19 - Kasnaeny Karim; Sattar Yunus; Muhammad Haerdiansyah Syahnur (Jurnal Abdi Insani, 2022)
Kreasi Rihlah Tourism Cooperative (Wasilah) is a service cooperative engaged in plant and vegetable processing services. With 20 members, this cooperative has not been able to develop a business on a par with other cooperatives. Marketing that still expects from visits to stores, human resource capabilities are still low. This condition was exacerbated by the Covid-19 pandemic at the beginning of 2020. This PKM activity is to provide education about entrepreneurial marketing. This education teaches production process improvements through the creation of Standard Operating Procedures, and the development of entrepreneurial skills in Cooperative HR. The materials consist of Business Model Canvas, preparation of SOPs, Product Standardization, Digital Marketing, Product Innovation, Entrepreneurship and Market access strategies, and Preparation of Financial Reports. The result of this PKM activity is an increase in participants' knowledge about the importance of making a business model canvas before starting a business, so that the business becomes focused. In addition, participants have been able to find out what are the strengths and weaknesses of their products, opportunities or challenges faced in doing business and how to explore product potential in order to be able to compete in the market. Participants also have additional knowledge about how to prepare SOPs and its importance for the smooth flow of production activities. It can be seen that there is an increase in the knowledge and abilities of cooperative human resources as evidenced by the selection of the best participants who are able to complete tasks during training. Thus, there has been a transfer of knowledge regarding entrepreneurial marketing, through the importance of compiling a Business Model Canvas. In addition, there has been an increase in HR capabilities in compiling SOPs, conducting online marketing, product innovation, entrepreneurial skills, and preparing financial reports to be able to access banking.